1978
DOI: 10.1111/j.1432-1033.1978.tb12739.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Spectral Properties of Putidamonooxin, the Iron‐Containing and Acid‐Labile‐Sulfur‐Containing Monooxygenase of a 4‐Methoxybenzoate O‐Demethylase from Pseudomonas putida

Abstract: Gel chromatography indicates that putidamonooxin has a molecular weight of about 126000. On the other hand, the amino acid composition and the iron‐to‐protein ratio point to a minimal molecular weight of 33000 and 31000 respectively. On sodium dodecylsulfate/polyacrylamide gel electrophoresis the enzyme migrated as a homogeneous band corresponding to a molecular weight of about 40000. The number of spots found in the tryptic peptide map of the carboxymethylated and digested enzyme indicates that putidamonooxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 36 publications
(23 reference statements)
1
16
0
Order By: Relevance
“…3 with a reduced amplitude. Binding of substrate to iron-depleted putidainonooxin as proved by visible absosption spectroscopy [3] does not influence this ESR spectrum. The incorporation of additional mononuclear non-heme iron centers strongly bound to its binding-site only in the presence of substrate leads to an increase in intensity of the resonance at g = 4.3.…”
Section: The Mononucleur Non-heme Iron Center In Putidumononxinmentioning
confidence: 99%
See 2 more Smart Citations
“…3 with a reduced amplitude. Binding of substrate to iron-depleted putidainonooxin as proved by visible absosption spectroscopy [3] does not influence this ESR spectrum. The incorporation of additional mononuclear non-heme iron centers strongly bound to its binding-site only in the presence of substrate leads to an increase in intensity of the resonance at g = 4.3.…”
Section: The Mononucleur Non-heme Iron Center In Putidumononxinmentioning
confidence: 99%
“…Partial uncouplers allow both types of reactions [4,6]. Chemical [2,3] and spectroscopic [7 -101 analysis revealed that both enzyme components contain iron-sulfur clusters as redox-active centers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the extinction coefficients for these enzymes at their respective A maxima are comparable. The value for the P. putidu monooxygenase at 455 nm is 14.7 mM-l cm-' (Bernhardt et al, 1978); that for CMO at 459 nm was estimated as 7 to 11 mM-' cm-' in different preparations, assuming the native molecular mass given below and using A,,, to estimate protein. These CMO values would be underestimates if the chromophore were damaged during protein purification.…”
Section: Mostmentioning
confidence: 99%
“…The loss of color upon addition of dithionite is also consistent with an Fe-S protein (Lovenberg, 1973). Although Fe-S proteins typically have a peak near 415 nm and CMO does not, the known exceptions include a monooxygenase from Pseudomonas putida (Bernhardt et al, 1978). The oxidized spec- Wavelength (nm) Figure 6.…”
Section: Mostmentioning
confidence: 99%